Effect of Anaemia and Transfusion on Outcomes in Mechanically Ventilated Infants and Children - Hossam Mohamed Abd Elkarem; Salah Mahmoud Saleh; Ahlam Mohamed Ismail; Nagwa Mohamed Sabry; Doaa El-Zaeem Ismail (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Anemia is a common problem in mechanically ventilated children, with consequences including prolonged duration of ventilation, high rates of morbidity, and increased deaths. Red cell distribution width (RDW) has become an important marker for prognosis, but blood transfusion, with its benefits, carries significant risks. Objective: To assess anemia, RDW, and transfusion practice impact on outcomes in mechanically ventilated pediatric patients and explore best practice for managing anemia and transfusion in such cases. Methods: An analysis was conducted for anemia classification, use of RDW for prognosis, and concomitant risks for transfusion. Several approaches, including restrictive transfusion triggers, use of erythropoiesis-stimulating drugs, and blood conservation techniques, have been evaluated. Results: Anaemia worsens pulmonary function, impedes successful weaning, and increases complications. Higher RDW reflects poor prognosis, but transfusion can improve oxygenation but with added complications in terms of pulmonary trauma and modulates the immune system. Targeted anemia management and restrictive transfusion protocols can contribute to positive patient outcomes. Conclusion: Successful anemia management in mechanically ventilated children will require a multi-disciplinary intervention. Future studies must explore refinement in transfusion triggers and improvement in non-transfusion therapy for enhancing survival and successful discharge.